PENGARUH KOMUNIKASI ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA BAGIAN PRODUKSI MIE INSTAN PT.INDOFOOD CBP SUKSES MAKMUR TBK CABANG PEKANBARU - R.Ayuningtyas Budiarti; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at PT. Indofood CBP Sukses Makmur Tbk cabang Pekanbaru branch research is the influence of organizational communication and organizational commitment to employee job satisfaction on the part of instant noodle production PT. Indofood CBP Sukses Makmur Tbk cabang Pekanbaru brand. purpose of this research is to know the organization communication, organizational commitment, job satisfaction employees and to know the influence of organizational communication to employee job satisfaction, influence organizational commitment to employee job satisfaction on the production of instant noodles PT. Indofood CBP Sukses Makmur Tbk cabang Pekanbaru.The author uses descriptive analysis method quantitative data collection using questionnaire samples used is random sampling source data uses is primary data or data obtained directly from the object of research and secondary data is data collected author from PT. Indofood CBP Sukses Makmur Tbk cabang Pekanbaru.The results of this study indicate that organizational communication an organizational commitment has a significant effect in employee job satisfaction on the of instant noodles PT. Indofood CBP Sukses Makmur Tbk cabang Pekanbaru.Keywords : organizational comunnication, organizational commitment, employee job satisfaction